1991
DOI: 10.1073/pnas.88.23.10921
|View full text |Cite
|
Sign up to set email alerts
|

Limited T-cell receptor beta-chain heterogeneity among interleukin 2 receptor-positive synovial T cells suggests a role for superantigen in rheumatoid arthritis.

Abstract: Rheumatoid arthritis (RA) is a disease affecting the synovial membranes of articulating joints that is thought to result from T-cell-mediated autoimmune phenomena. T cells responsible for the pathogenesis of RA are likely present in that fraction of synovial T cells that expresses the interleukin 2 receptor (IL-2R), one marker of T-cell activation. We report herein an analysis of T-cell receptor (TCR) beta-chain gene expression by IL-2R-positive synovial T cells. These T cells were isolated from uncultured syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
119
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(129 citation statements)
references
References 44 publications
9
119
1
Order By: Relevance
“…This biased V gene pattern is due to the selective expansion of a monoclonal or oligoclonal T cell population(s) in patients with RA. The majority of predominant TCR AV and BV gene families expressed by hsp65-specific T cells from RA patients seen in our study correspond to the V genes found to be overexpressed in rheumatoid synovium (19,20,25,26).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This biased V gene pattern is due to the selective expansion of a monoclonal or oligoclonal T cell population(s) in patients with RA. The majority of predominant TCR AV and BV gene families expressed by hsp65-specific T cells from RA patients seen in our study correspond to the V genes found to be overexpressed in rheumatoid synovium (19,20,25,26).…”
Section: Discussionsupporting
confidence: 62%
“…Supporting evidence includes the HLA-DR association of the disease and the infiltration of T lymphocytes found in the lesions. There is evidence suggesting an overexpression of certain TCR V gene families among infiltrating T cells obtained from rheumatoid synovium (18)(19)(20). It is a subject of controversy, however, whether these infiltrating T cells are of oligoclonal or polyclonal origin (19,21,22), and their antigen specificity remains a matter of speculation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have provided a number of crucial insights. First, both the V ␤ usage and the T cell clonality appeared to be skewed in RA (45). Second, this skewing is a primary event, rather than merely a consequence of inflamma- tion, since the unaffected siblings of RA patients also display expanded T cell clonotypes (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The joint-restricted CD4 ϩ T cell clonotypes that persist over time are preferentially found in the CD25 ϩ subpopulation (5). Skewing of the TCRV␤ repertoire (e.g., V␤3, V␤14 ␣ ␦ V␤17) has been shown to occur frequently in CD25 ϩ T cells in the synovial fluid, indicating a local activation by a common antigenic stimuli (6). However, it has been difficult to identify clones of arthritogenic T cells or a common Ag in the joint that could explain the development of arthritis, and the pathogenic function of infiltrating T cells into the joint synovia is still uncertain.…”
mentioning
confidence: 99%